Rapid detection of viable Vibrio Cholerae by Bacteriophage - Rashid, Nafisa; Ul Haque, Naim; Sakib, Ahsan (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology 2022.